2006
DOI: 10.1002/ajpa.20361
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Fully technique for estimating statures

Abstract: The "anatomical" method of Fully (1956 Ann. Legale Med. 35:266-273) for reconstructing stature, involving the addition of skeletal elements from the calcaneus to the skull, has been increasingly used in anthropological and forensic contexts, but has undergone little systematic testing on samples other than the original sample used to develop the technique. The original description by Fully of the method also does not provide completely explicit directions for taking all of the necessary measurements. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
355
0
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(378 citation statements)
references
References 47 publications
8
355
0
15
Order By: Relevance
“…This method does not rely on calculating stature from a single long bone using regression formulae (the “mathematical method”), but instead produces an estimate based upon the measurement of all of those bones that contribute to height (Raxter et al, 2006, 2007; Maijanen, 2009; Auerbach and Ruff, 2010; Auerbach, 2011; Vercellotti et al, 2014). This provides a more accurate method of calculating living stature, as it is not biased by differences in bodily proportions (Maijanen, 2009; Auerbach and Ruff, 2010; Vercellotti et al, 2014).…”
Section: Research Rationalementioning
confidence: 99%
“…This method does not rely on calculating stature from a single long bone using regression formulae (the “mathematical method”), but instead produces an estimate based upon the measurement of all of those bones that contribute to height (Raxter et al, 2006, 2007; Maijanen, 2009; Auerbach and Ruff, 2010; Auerbach, 2011; Vercellotti et al, 2014). This provides a more accurate method of calculating living stature, as it is not biased by differences in bodily proportions (Maijanen, 2009; Auerbach and Ruff, 2010; Vercellotti et al, 2014).…”
Section: Research Rationalementioning
confidence: 99%
“…Whichever reference population(s) approach is preferred, results clearly vary depending on the model type regression and statistical technique used (Olivier, 1976;Feldesman and Lundy, 1988;jungers, 1988;Feldesman et al, 1990;Aiello, 1992;Konigsberg et al, 1998;Hens et al, 2000;Porter, 2002;Raxter et al, 2006). Indeed, for some authors the choice of reference sample is considered a purely statistical issue (Kendall and Stuart, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Studies [3][4][5][6][7][8][9] have shown that race, age, sex, environment and nutrition affect not only the stature but also different body proportions and the differences found in the present study may be due to these factors.…”
Section: Estimation Of Stature From Percutaneous Length Of Ulna and Tmentioning
confidence: 62%
“…[2,3] Though, anatomical method is more accurate, but often complete skeletal remains are unavailable from a crime scene and therefore, the forensic anthropologists as well as medicolegal experts have to reconstruct stature from the relatively less precise mathematical method, which is workable even if only a single long bone is available. [4][5][6] Professor Karl Pearson (1898-99) was the first to introduce correlation calculus for stature prediction from long bones. [6] Stature estimation from long bones length offers an important contribution to identification of unknown remains, as there exists an important relationship between different body parts dimensions and stature, particularly bone lengths.…”
Section: Introductionmentioning
confidence: 99%